Al-Quran Sebagai Sumber Kisah: Mengasah Keterampilan Memproduksi Kisah Bagi Pendidik Anak Usia Dini - Hidayati, Laily (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
One of the main contents of the holy Quran is the story or history of the past, which is explainedin the purpose of the revealed Quran as a guide and guidance for the life of the human being,then the Quran verses story are to be learned as a lesson so that human can easily carry out thetasks of creation throughout their life span. The human life span is calculated since he was borninto this world with the age of 0 years until the end of his life, which includes infancy, childhood,adolescence, adulthood, elderly, until the end of one's age. In that age range, DevelopmentalPsychologists have agreed that there is a period in a human's life span, which is considered themost crucial and most important period as a basis for the formation of human beings who willsail the ark of life throughout their lives. The period is known as the golden age or